Estimating the transmission dynamics of dengue fever in subtropical Malaysia using seir model - Emmanuel, Sabastine; Saratha Sathasivam; Majid Khan Majahar Ali; Tan, Jin Kee; Yap, Sze Ling (Penerbit Universiti Kebangsaan Malaysia, 2023)
In this study, we utilized the SEIR model in conjunction with Heun's predictor-corrector method to analyze the transmission dynamics of dengue fever over time in subtropical Malaysia. Our main focus was on estimating the recovery rate of the infected population and gaining insights into the patterns of disease spread. By applying Heun's method to the SEIR model, we were able to provide more accurate estimations and a comprehensive understanding of the dynamics of dengue fever. We examined the population dynamics of susceptible, exposed, infectious, and recovered individuals, and analyzed the effectiveness of intervention measures. Through our analysis, we not only uncovered the patterns of disease transmission but also shed light on the impact of various control measures. Our findings contribute to the existing knowledge and offer valuable insights into managing and controlling the spread of dengue fever in subtropical regions like Malaysia.